Standarization Of Pinyaram Banana Recipes As A Traditional Cakes In Kenagarian Salayo Solok Regency - Anisa Amalia; Wiwik Gusnita (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study intends to standardize the shape, color, scent, texture, and taste of banana pinyaram in Kanagarian Salayo, Solok Regency. This standardization was carried out in order to characterize and examine the shape, color, scent, texture, and taste of banana pinyaram. This study aimed to standardize the banana pinyaram recipe in Kenagarian Salayo, including the components, amount of ingredients, preparation method, and quality. The Mixed Approach research method was employed, which is a mix of quantitative and qualitative methods. Direct trials on the production of banana pinyaram are a quantitative method. The qualitative method entails interviewing the informants and making observations. On (December 15, 2021 – January 15, 2022) this study was conducted in four jorongs in Kanagarian Salayo, Kubung District, Solok Regency, and the Catering Workshop. A completely randomized design (CRD) with three repetitions was used in this qualitative investigation. The primary data was collected directly from three expert panelists who responded to an organoleptic test format on the standardized quality of banana pinyaram in Kanagarian Salayo, Solok Regency, which was then tabulated into a table format and analyzed to see the differences between the ten recipes that would be standardized by the t test. In qualitative research, the informants are interviewed and observations are made. Shape (neat semi-circle) 3.67, color (dark brown) 3.89, scent (fragrant banana) 3.56, texture (chewy) 3.67, and flavor (sweet) 3.33 were the average values.